EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Setiani, Henny; Larasati, Anisa; Amalia, Ina; Noviar, Lisda; Romdonah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The aim of this study is to analyse the extent to which problem-based learning (PBL) contributes to improving critical thinking skills among primary school pupils. The background to this study is the fact that pupils’ critical thinking skills remain at a low level, as teacher-centred teaching still predominates. As part of this study, a literature review was conducted by evaluating academic journals and relevant books from the past ten years. The results of the study indicate that the implementation of the PBL model can enhance pupils’ critical thinking skills in the form of improved problem-analysis skills, the ability to express opinions, and the ability to make logical decisions. Furthermore, PBL encourages pupils to take the initiative in the learning process. Therefore, it can be concluded that the problem-based learning (PBL) model is effective in enhancing the critical thinking skills of primary school pupils.